1956
DOI: 10.1017/s0021859600040351
|View full text |Cite
|
Sign up to set email alerts
|

The response of different types of pigs to varying levels of feeding from weaning to bacon weight, with particular reference to carcass quality

Abstract: 1. A review of the literature indicated: (a) A lack of agreement upon whether or not restriction of the plane of feeding from weaning or 100 lb. live weight to bacon weight improves efficiency of food conversion. (b) That a severe restriction of the plane of feeding improves carcass-quality measurements, (c) That a less severe restriction of food intake brings the total growth period within a range more acceptable to the farmer, but only has a small effect in improving carcass quality, (d) That the small benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
4

Year Published

1957
1957
1980
1980

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 24 publications
5
38
4
Order By: Relevance
“…The results obtained in this experiment are in general agreement with the findings of Lucas & Calder (1956), who investigated in detail the question of the effect of level of feeding and type of pig on carcass quality under conditions where all pigs were fed individually twice daily.…”
Section: Discussionsupporting
confidence: 90%
“…The results obtained in this experiment are in general agreement with the findings of Lucas & Calder (1956), who investigated in detail the question of the effect of level of feeding and type of pig on carcass quality under conditions where all pigs were fed individually twice daily.…”
Section: Discussionsupporting
confidence: 90%
“…These measurements were taken as described by Lucas & Calder (1956), except that they were on carcasses which had been chilled for about 24 hr. after slaughter, and which had not yet been cured in brine tanks.…”
Section: Methodsmentioning
confidence: 99%
“…A diagram of these huts, runs and feeding compartments has been given in Appendix Fig. 2 of a previous report (Lucas & Calder, 1956). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cunningham et al (1962) concluded that the period of adaptation has little influence on the pig's ability to digest cellulose. However, Friend et al (1962) (Lucas and Calder 1956;Troelsen and Bell 1962;Vanschoubroek et al 1967) or where changes in palatability arise from excessive levels of, or inhibitory substances (Hanson et al 1956) For personal use only.…”
Section: Dietary Fiber and Performancementioning
confidence: 99%